Studi Eksploratif tentang Pemeliharaan Berkala dan Dampaknya terhadap Kinerja Operasional di UD Sandi Jaya Transportasi - Kurniawan Sandi; Agung Dwi Nugroho (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Periodic maintenance strategies play a crucial role in ensuring vehicle reliability and enhancing operational efficiency in the transportation sector. This study aims to examine the implementation of routine maintenance on the truck fleet of UD Sandi Jaya Transportasi and to analyze its impact on the company’s operational performance. The research adopts an exploratory study design using a descriptive qualitative approach. The objects of study include four operational truck units, with data collected through field observations, in-depth interviews, and documentation of maintenance records and vehicle breakdown history. Data analysis refers to the Reliability Centered Maintenance (RCM) method and Failure Mode and Effects Analysis (FMEA) to identify critical components and determine optimal maintenance intervals. The findings indicate that the absence of scheduled maintenance leads to increased operational costs and vehicle downtime, whereas implementing a periodic maintenance schedule improves fleet availability and reduces the frequency of technical failures. This research offers practical insights for developing maintenance management systems in small- to medium-scale transportation enterprises.